2023
DOI: 10.1186/s12917-023-03640-1
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of methicillin-resistant Staphylococcus species in healthy and sick pets: prevalence and risk factors

Abstract: Background The characterization of staphylococcal species that colonize pets is important to maintain animal health and to minimize the risk of transmission to owners. Here, the prevalence of Staphylococcus spp. and methicillin resistance was investigated in canine and feline isolates, and risk factors of staphylococcal colonization were determined. Pets were examined and separated into four groups: (1) healthy dogs, (2) healthy cats, and (3) dogs and (4) cats with clinical signs of bacterial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
4
0
0
Order By: Relevance
“…and Mammaliicoccus sciuri in our study (69%) aligns with that reported in previous studies [42,43]. In line with this, it has also been seen that both healthy and diseased companion animals harbor both CoPS and CoNS, although certain species showed a stronger association with each animal species [43]. In this study, CoPS, such as S. pseudintermedius, were more frequently isolated from dogs, while CoNS, including S. felis, were more commonly isolated from cats, as reported previously [42][43][44][45].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…and Mammaliicoccus sciuri in our study (69%) aligns with that reported in previous studies [42,43]. In line with this, it has also been seen that both healthy and diseased companion animals harbor both CoPS and CoNS, although certain species showed a stronger association with each animal species [43]. In this study, CoPS, such as S. pseudintermedius, were more frequently isolated from dogs, while CoNS, including S. felis, were more commonly isolated from cats, as reported previously [42][43][44][45].…”
Section: Discussionsupporting
confidence: 93%
“…The overall observed prevalence of Staphylococcus spp. and Mammaliicoccus sciuri in our study (69%) aligns with that reported in previous studies [ 42 , 43 ]. In line with this, it has also been seen that both healthy and diseased companion animals harbor both CoPS and CoNS, although certain species showed a stronger association with each animal species [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations